Against the Consensus : Reflections on the Great Recession / [electronic resource] - Lin, Justin Yifu (Cambridge : Cambridge University Press, 2013)
In June 2008, Justin Yifu Lin was appointed Chief Economist of the World Bank, right before the eruption of the worst global financial and economic crisis since the Great Depression. Drawing on experience from his privileged position, Lin offers unique reflections on the cause of the crisis, why it was so serious and widespread, and its likely evolution. Arguing that conventional theories provide inadequate solutions, he proposes new initiatives for achieving global stability and avoiding the recurrence of similar crises in the future. He suggests that the crisis and the global imbalances both originated with the excess liquidity created by US financial deregulation and loose monetary policy, and recommends the creation of a global Marshall Plan and a new supranational global reserve currency. This thought-provoking book will appeal to academics, graduate students, policy makers, and anyone interested in the global economy.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Global Financial Crisis, 2008-2009